EFEKTIVITAS INFUSA KULIT JERUK PURUT (Citrus hystrix DC.) TERHADAP PERTUMBUHAN Candida albicans PENYEBAB SARIAWAN SECARA in vitro - Zakiyatul Khafidhoh; Sri Sinto Dewi; Arya Iswara (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2015)
Candida albicans is a normal flora in the oral mucosa, tongue, and palate, but it could become the pathogenic one. If the amounts were excess so that it could cause thrush. Kaffir lime peel infusion contains saponins, tannins, flavonoids, coumarin which are active antifungal compound. The purpose of this study was to examine the effectiveness of kaffir lime peel infusion to the growth of Candida albicans which causes thrush with a consentration of 10%, 15%, 20% and contact time of 5 minutes, 10 minutes, 15 minutes. Method of this study used an experimental research laboratory. Suspension Candida albicans 100 mL with dilution 10-4 of McFarland 0,5 and contacted to the kaffir lime peel infusion 10%, 15%, 20% with three repetitions. After 5 minutes, 10 minutes, and 15 minutes put 100 μL and then inoculated into SGA antibiotics then incubated at 37˚C for 48 hours. Based on the results of this study concluded that kaffir lime peel infusion can inhibit the growth of Candida albicans. The best results was the 20% consentration and contact time of 15 minutes with an average colonies of 3×104 CFU/100 μL. The higher consentration of kaffir lime peel infusion the more able to inhibit the growth of Candida albicans and the longer the contact time kaffir lime peel infusion, the more can inhibit the growth of Candida albicans.Keywords: Infusion, Citrus hystrix DC., Candida albicans.